(untitled) (Revista de Ciências Agroveterinárias, 2020)
In order to maximize bee pollen collection in the hives, management of colonies of Africanized bees (Apis mellifera L.) must respect harvest intensity and the species’ biological aspects and implement innovations that optimize production. Accordingly, this study set out to compare the bee pollen productivity between two different pollen trap models and the productivity in the use of one or two pollen traps in the hive. The following treatments were applied: a front-mounted trap fitted at the hive entrance, a top-mounted pollen trap above the hive, and two – one front-mounted and one top-mounted – pollen traps on the same hive. All of the colonies were subjected to all of the treatments to circumvent the colony’s effect on productivity results. The front-mounted pollen trap indicated the highest bee pollen productivity, and the colonies only needed one pollen trap to demonstrate productive potential in the Caatinga.